Implementation of Child Detention Rights in the State Prison Class 1A Cirebon - Susilowati, Detri; Triyadi , Septiyan Bayu; Ramadhanty , Rafifah; Waluyadi , Waluyadi; Karina , Karina (PT FORMOSA CENDEKIA GLOBAL, 2025)
Child protection is essential because children are the most vulnerable members of society, and they can live in peace. Children who are neglected by their families or society will be disrupted in their growth and development, both physically, mentally, and socially. This study aims to analyze the implementation of the rights of Children in the Face of the Law (ABH) in the Cirebon Class 1A State Prison. This study uses a normative juridical approach. Data was collected through a literature study of the Law and interviews with Cirebon Class IA State Prison officers. The study's findings show that several rights of Children in Conflict with the Law (ABH) have been met, including services such as decent food, bedding, worship, and legal assistance, as well as health care, informal education, and guidance. However, the right to training is still not optimally fulfilled due to the limitations of available facilities and programs. Implementing the SPPA Law is very important to ensure humane treatment, access to education, and skills training for ABH. This research emphasizes the need to improve facilities and develop training programs to support the development of ABH during the detention period. Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, which guarantees humane treatment and access to education and skills training for ABH, must be implemented to the maximum extent.